"mecum, cum mecum, conmigo" and "con mí": linguistic knowledge and prestige-morphology - Jodl, Frank (Revista de Filología Románica, 2019)
Interpreting the Codex emilianense Em 31 and the Latin-Latin glossary included in it (scriptorium San Millán de la Cogolla, 10th or 11th century), Claudio García Turza (2004, 112s.) emphasizes, among other things, the entry cum me that the gloss compares to mecum. Due to the fact that neither of the two forms has survived in modern Spanish, I shall attempt to trace back the origins of the imposing (pleonastic) form cum mecum, i.e. conmigo, basing my assumptions on the metalinguistic comment represented by the gloss. My goal will be to illustrate that the phenomenon in question can be explained by the prestige morphology concept (Jodl 2006, 12-16 and Jodl 2018, 275-280), which can furthermore be used to complete the current linguistic change theories in general.